Venous valve stent design - Low, Jun Yu (2019)
Chronic venous insufficiency (CVI) is a condition whereby the venous valves fail to function as intended and this results in retrograde blood flow. This affects the efficiency of blood flowing from the lower extremities of the human limbs back to the heart. Hence, there is a need to design a stent that can accommodate the suturing of artificial venous valve to replace the native venous valves, particularly in the great saphenous vein.